2018
DOI: 10.1021/acs.orglett.8b02419
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Dual C(sp2)–H Functionalization of Indole-2-carboxamides Involving a 1,2-Acyl Migration: A Synthesis of Indolo[3,2-c]quinolinones

Abstract: A novel Pd/Cu catalytic system to construct indolo[3,2- c]quinolinones has been developed starting from indole-2-carboxamides. Substrates were transformed into indolo[3,2- c]quinolinones through dual C(sp)-H functionalization of the indole moiety and arene, in which a carbonyl 1,2-migration was involved. The corresponding products were obtained in moderate to excellent yields with a wide substrate scope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 70 publications
0
16
0
1
Order By: Relevance
“…Recently, Lingkai and his colleagues developed an efficient method to construct indolo[3,2- c ]quinolinones starting from indole-2-carboxamides in the presence of a Pd-catalyst. 8 From our point of view, the methodology is ideally suitable for a multicomponent reaction. Therefore, our aim is to use easily accessible starting materials in a Ugi four-component reaction followed by a tandem/sequential Pd(OAc) 2 -catalyzed dual C(sp 2 )–H functionalization of the Ugi products toward indolo[3,2- c ]quinolinone analogues, involving a 1,2-acyl migration.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Lingkai and his colleagues developed an efficient method to construct indolo[3,2- c ]quinolinones starting from indole-2-carboxamides in the presence of a Pd-catalyst. 8 From our point of view, the methodology is ideally suitable for a multicomponent reaction. Therefore, our aim is to use easily accessible starting materials in a Ugi four-component reaction followed by a tandem/sequential Pd(OAc) 2 -catalyzed dual C(sp 2 )–H functionalization of the Ugi products toward indolo[3,2- c ]quinolinone analogues, involving a 1,2-acyl migration.…”
mentioning
confidence: 99%
“…A plausible mechanism of the cyclization path was explained based on the previous report as shown in Scheme 5. 8 After obtaining the Ugi adduct 5a , Pd(OAc) 2 attacks the indole to give the iminium intermediate A , which undergoes a nucleophilic attack of the N -aryl to the iminium moiety which forms the intermediate B . Then B is further converted to the intermediate C via a nucleophilic addition process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Base-promoted C → N acyl migration was used by Vicario and co-workers for the synthesis of nonproteinogenic tertiary and quaternary N-alkyl α-amino acids [13]. In a recent work by Kong et al,indolo[3,quinolinones were synthesized via a Pd/Cu catalyzed 1,2-acyl migration, starting from indole-2-carboxamides [14]. The methods reported thus clearly demonstrate the applicability of acyl rearrangement in diverse synthetic routes.…”
Section: Introductionmentioning
confidence: 88%
“…6 Recently, the group of Li reported that 1-sulfonyl-4-(2-acetoxyethyl)-1,2,3-triazoles underwent 1,3-acetoxy migration to give substituted cyclopropanes (Scheme 1c). 7,8 During our ongoing investigation on the synthetic transformations triggered by α-imino metal carbenoids, we found that ring expansions of 2-triazolyl-1-indanone derivatives proceeded via 1,2-acyl migration, 9 which was hardly seen in carbene-induced reactions. We report here that these reactions provide a unique method for the synthesis of substituted 1-naphthols, which constitute an important class of bicyclic compounds widely found in many natural and synthetic products.…”
mentioning
confidence: 99%